The Role of Published Materials in Marketing of Information in Institutions. A Case Study of National Teachers College in Kabale Municipality - Doreen, Arineitwe (Kabale University, 2019)
A Research Report Submitted to the Faculty of Arts and Social Science in Partial Fulfillment of the Requirement for the award of Diploma in Library and Information Science of Kabale University